STEPMOTHER MYTH IN WOLIO FOLKTALE PUTIRI SATARINA - Mulawati, NFN (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
Objection of this research are describing surface and deep structure of step mother’s myth in Wolio’s folktale hope that this research could give some advantages in giving a new paradigm in sciences especially about myth and folktale. The step of analysis are reading in order to get first impression about the story. After that, the researcher divided the story into some episodes, arranging those story’s episodes according to syntagmatic and paradigmatic term, describing some opotitional relation of story’s episode, giving some interpretation to those relation based on etnografic data of community who own the story. The result of the research showed that this folktale describe surface structure such as character and characterization, plot of the folktales, and setting of the folktales. The difference could be seen on main character which act in those folktales, they have different name but in same sex. This research is also describing the deep structure of the folktale, deep structures is relating with some Wolionese cultural values. Those deep structures were not change although the surface structure were transformed. Beside that, the researcher found another deep structure such as the effort of Wolionese maintain good behavior toward god and human. Those effort was supported by some life cycle ritual and religion ceremony which contain life values. Those rituals objection is preserving harmony between human and universe. Those folktales also contain ecological reality of Wolionese and Munanese community.